Introduction to mineralogy and petrology - Haldar, S. K. (Elsevier, 2014)
Presents the essentials of mineralogy and petrology, including crystal structure, formation and grouping of minerals and soils, definition, origin, structure and classification of igneous, sedimentary and metamorphic rocks. Provides accessible, step-by-step guidance to exploring, retaining, and implementing the core concepts of mineral and hydrocarbon exploration, mining, and extraction.